Employment of mixed mode in single-layer microstrip antenna for ISM/WiMAX/WLAN/4G/Sub 6 GHz 5G mobile communication. Issue 7 (2nd May 2020) - Sarkar, Tanmoy; Ghosh, Abhijyoti; Chakraborty, Subhradeep; Singh, L. L. K.; Chattopadhyay, Sudipta
ABSTRACT: The design and development of multiband antenna for useful operating bands are the current state-of-the-art research in the field of antenna research. A simple and single-layer printed multiband radiation structure eliminates the packaging complexity of modern communication devices. The present investigation proposes such simple and single-layer multiband antenna for ISM 2.5 GHz/WiMax 3.5 GHz/WLAN 5.2 GHz/ISM 5.8 GHz wireless application for 4G LTE and sub 6 GHz 5G spectrum. The proposed antenna can completely cover the required frequencies with good radiation characteristics at the broadside direction. The design has been carried out using the RT duroid 5870 substrate ( ϵ r  = 2.33, height h  = 1.575 mm) for simulation and measurements. In the proposed patch antenna, the slots have been judiciously used to employ mixed modal behaviour which capitulates multiple useful bands with proper bore-sight radiation.